Commercial seed corn breeding - Hull, R. W. (My University, 1908)
Introduction: The growing of pure bred corn for the purpose of selling it as seed is fast becoming recognized as an important branch of agriculture. Corn growers are rapidly coming to realize that good seed is of great economic value. As land increases in price this difference between the value of good and of pure seed increases.
Citation: Hull, R. W. Commercial seed corn breeding. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Agriculture; Farming; Corn; Seeds; Graduating theses; Senior theses; Theses